2D high speed machining simulations using a new explicit formulation with linear triangular elements. (14th April 2011) - De Micheli, P.O.; Mocellin, K.
This paper presents the several advantages of a new explicit formulation using modified linear tetrahedral elements non-sensitive to volumetric locking in the scope of high speed machining simulations. First, the explicit time integration allows obtaining very interesting computational time in very dynamic cases with complex behaviour laws. Then, the use of a tetrahedral mesh permits to use robust non-structured adaptive remeshers too. No chip separation criteria or damage model is used. Our 2D orthogonal cutting model detects automatically the apparition of an adiabatic shear band, and simulates very precisely its evolution and the chip formation. Phenomena relative to adiabatic shearing bands already described in the literature can be observed in detail in the simulation. This model is a powerful tool to improve the understanding of chip formation and adiabatic shear band propagation, and to simplify the optimisation of high speed machining processes in industries.